If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 439 = (x + -58) * 2 Reorder the terms: 439 + x = (x + -58) * 2 Reorder the terms: 439 + x = (-58 + x) * 2 Reorder the terms for easier multiplication: 439 + x = 2(-58 + x) 439 + x = (-58 * 2 + x * 2) 439 + x = (-116 + 2x) Solving 439 + x = -116 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 439 + x + -2x = -116 + 2x + -2x Combine like terms: x + -2x = -1x 439 + -1x = -116 + 2x + -2x Combine like terms: 2x + -2x = 0 439 + -1x = -116 + 0 439 + -1x = -116 Add '-439' to each side of the equation. 439 + -439 + -1x = -116 + -439 Combine like terms: 439 + -439 = 0 0 + -1x = -116 + -439 -1x = -116 + -439 Combine like terms: -116 + -439 = -555 -1x = -555 Divide each side by '-1'. x = 555 Simplifying x = 555
| 2(m+4)=m+2 | | 78+r=-76 | | 151(57457+9)+9252=1 | | x=x^2-x-12 | | 6(x+3)=10 | | ln(x+2)+ln(x)=ln(x+12) | | 0.50x+0.35(50)=47.5 | | 6(x-3)=10 | | -12/9-30/-12= | | 3f+15=51 | | -2.8=w | | 400*400= | | x*x+1200=2x*2x | | R(6-s-t)+6p(6-s-t)= | | -2c+2=5c | | 3=14+2x | | 6x+(x+1)=5(x+1) | | 4x^2-5x+9=2x+6 | | x+x+x+x=30 | | -(-n)=1 | | y=7x-53 | | 7(m-n)+p(m-n)= | | 3(e+2)=e-6 | | 16x-277=6x-7 | | 150m+2500=125m+3000 | | 150m+2500=125m+3,000 | | 16h+800=21h+720 | | 7z-3+z=-9 | | 4(x+7)+3y(x+7)= | | 100d+1200=-190d+3230 | | 5-(2d-4)=6 | | 2(8-4x)=0.33333333333(33-18x)+3 |